Biometric Recognition System: A Review - Kaur, Manpreet; Singh Khurmi, Sawtantar (International Journal of Computer Sciences and Engineering, 2025)
Biometric system is used for identification of an individual on the basis of their physical and behavioral features. As the research in the information technology is increasing day by day, so, the security of information becomes a great issue. Therefore, to deal with security, authentication access control plays an important role and this is the first step to ensure security. This paper describes the study of widely used biometric technologies. The principle by the biometric system work is being defined with the stages by which biometric system works. In biometrics, according to some characteristics, we need to identify human physiological parameters. The comparison of biometric traits on the basis of feature description is given with their characteristics on the basis of uniqueness, university, measurability, acceptability, circumvention and premenance. Work done by number of authors in biometric system is given in the form of comparison with the techniques and outcomes. A biometric system requires a reliable personal identification scheme to confirm or determine the needs of their individual identity services. The aim of this technique is to ensure that only legitimate users can access these services, and are not accessible to others. The notable features of biometric can be confirmed or established a personal identity.